2017
DOI: 10.1186/s13000-017-0621-8
|View full text |Cite
|
Sign up to set email alerts
|

Targeted sequencing may facilitate differential diagnostics of pulmonary tumours: a case series

Abstract: BackgroundHistopathological diagnosis is important for prognostication and choice of treatment in patients with cancer in the lung. Metastases to the lungs are common and need to be distinguished from primary lung cancer. Furthermore, cases with synchronous or metachronous primary lung cancers (although infrequent) are often handled differently than cases with lung cancer with intrapulmonary metastasis or relapse, respectively. In some cases, morphology and immunohistochemical staining is not sufficient for ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…The ORR for extracranial lesions in patients with CNS metastases treated with furmonertinib has been found to be 77% ( 26 ), exceeding the ORRs of 56% in patients treated with osimertinib ( 27 ) and 61.5% in patients treated with aumolertinib ( 35 ). A case series in NSCLC has reported that ineffective TKI treatment could be explained in part by the discordance of molecular genetic profiles in lung adenocarcinoma with intrapulmonary metastases ( 36 ). We considered the possibility that extracranial resistance to furmonertinib could be attributed to the coexistence of the T790M mutation with other subclones.…”
Section: Discussionmentioning
confidence: 99%
“…The ORR for extracranial lesions in patients with CNS metastases treated with furmonertinib has been found to be 77% ( 26 ), exceeding the ORRs of 56% in patients treated with osimertinib ( 27 ) and 61.5% in patients treated with aumolertinib ( 35 ). A case series in NSCLC has reported that ineffective TKI treatment could be explained in part by the discordance of molecular genetic profiles in lung adenocarcinoma with intrapulmonary metastases ( 36 ). We considered the possibility that extracranial resistance to furmonertinib could be attributed to the coexistence of the T790M mutation with other subclones.…”
Section: Discussionmentioning
confidence: 99%
“…30 NGS is now emerging as a potential tool for determining clonality of tumor in clinical care, in which routine investigation and older mutational profiling techniques prove inconclusive. Ericson-Lindquist et al 31 reported a recent series of six cases in which pyrosequencing or NGS was used to determine clonality to other lung cancers or distant primaries.…”
Section: Discussionmentioning
confidence: 99%